2020
DOI: 10.1111/jth.14874
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted role of glycosylation in transfusion medicine, platelets, and red blood cells

Abstract: The conjugation of carbohydrate moieties, or saccharides, onto various glycosyl acceptors, be it a protein, lipid, or any organic molecule, defines glycosylation. It is a very prevalent posttranslational nontemplated modification. Glycosylation is highly modular; carbohydrate building blocks are repeatedly linked and assembled in varying lengths, branches, and configurations. Being nontemplated, glycosylation does not have canonical patterns, which can result in high diversity and an extensive repertoire of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 126 publications
(255 reference statements)
2
27
0
Order By: Relevance
“…For instance, regarding the apoptosis-related Bcl/Bax proteins (C 18 ) involved in platelet clearance 49 , the isoforms BNIP2, BCL2L1 (BCL-XL or BIM), BAD and BAK1 are present in the current proteome, while also the transcripts of BLC7B, BCL9 and BCL2 are highly expressed. As another example, regarding the glycosyl transferases (C 16 ) and epimerases (C 12 ) implicated in the surface glycosylation pattern and thereby in platelet survival time 50 , prominently present in the proteome (transcriptome) are GALM, GALE, GNE, C1GALT1 and B4GALT1/3/4/5/6, while C1GALT1C1 (COSMC) is only lowly transcribed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, regarding the apoptosis-related Bcl/Bax proteins (C 18 ) involved in platelet clearance 49 , the isoforms BNIP2, BCL2L1 (BCL-XL or BIM), BAD and BAK1 are present in the current proteome, while also the transcripts of BLC7B, BCL9 and BCL2 are highly expressed. As another example, regarding the glycosyl transferases (C 16 ) and epimerases (C 12 ) implicated in the surface glycosylation pattern and thereby in platelet survival time 50 , prominently present in the proteome (transcriptome) are GALM, GALE, GNE, C1GALT1 and B4GALT1/3/4/5/6, while C1GALT1C1 (COSMC) is only lowly transcribed.…”
Section: Discussionmentioning
confidence: 99%
“…This study also confirmed the higher risk in blood group A than in other blood groups (odds ratio [OR] 1.45; 95% CI 1.20–1.75) and a protective effect in blood group O versus the other blood groups (OR 0.65; 95% CI 0.53–0.79) [74]. These findings could be due to elevated vWF levels in non-group O individuals, which predispose to thromboembolic events, as has been well-described prior to the current pandemic [75].…”
Section: Endothelium Von Willebrand Factor and Abo Blood Groupmentioning
confidence: 99%
“…Supporting the importance of sialyl transferases in the platelets’ lifespan, mice lacking ST3GAL4 (an enzyme that transfers sialic acid onto β1,4-galactose) develop thrombocytopaenia due to increased platelet clearance via the hepatic Ashwell–Morell receptor [ 32 ]. Moreover, the lack of ST3GAL1 (an enzyme that caps the Thomsen–Friedenreich antigen with sialic acid) was associated with platelet counts 50% lower than normal, as observed in ST3GAL1-null mice [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 98%